Temporal integration of auxin information for the regulation of patterning - Galvan-Ampudia, Carlos; Cerutti, Guillaume; Legrand, Jonathan; Brunoud, Géraldine; Martin-Arevalillo, Raquel; Azais, Romain; Bayle, Vincent; Moussu, Steven; Wenzl, Christian; Jaillais, Yvon; Lohmann, Jan U.; Godin, Christophe; et al. (eLife, 2020)
Positional information is essential for coordinating the development of multicellular organisms. In plants, positional information provided by the hormone auxin regulates rhythmic organ production at the shoot apex, but the spatio-temporal dynamics of auxin gradients is unknown. We used quantitative imaging to demonstrate that auxin carries high-definition graded information not only in space but also in time. We show that, during organogenesis, temporal patterns of auxin arise from rhythmic centrifugal waves of high auxin travelling through the tissue faster than growth. We further demonstrate that temporal integration of auxin concentration is required to trigger the auxin-dependent transcription associated with organogenesis. This provides a mechanism to temporally differentiate sites of organ initiation and exemplifies how spatio-temporal positional information can be used to create rhythmicity.
Gesehen am 10.06.2020